The analysis of work improvement of short ergonomics break on the rice weeding farmers in Kebon Bantiran, Bajera, Tabanan - I Nengah Darma Susila; I Ketut Sutapa; I Nyoman Sutarna (Unit Publikasi Ilmiah, P3M Politeknik Negeri Bali, 2021)
Weeding rice in paddy fields is mostly done by female farmers, as it is done by farmers in Kebon Bantiran village, Bajera, Tabanan. The body position of the female farmers when weeding the rice in the paddy field is bent and both feet are buried in the mud. The purpose of this study was to find out and describe the workload of female farmers when weeding rice plants in the rice fields. The sample for this study is 10 female farmers. The method of this research is the measurement of pulse with the 10 pulse-method. Data collection is done twice, after-work and after a short break. The data obtained are analysed by a t-paired test. The calculation results obtained the mean after-work pulse rate of 115.25 pulse per minute, while the resting pulse rate was 95.50 pulse per minute, decreased pulse rate was 19.75 pulse per minute or decreased by 20.68 percent. In the statistical test, the t-paired test decreased significantly (p is less than 0.05). The workload of female farmers to weed rice is a mild category. The percentage of cardiovascular load (CVL) for female farmers when weeding rice was 19.99 percent which indicates the category required for work improvement. The percentage of CVL value is calculated from the level of workload classification based on the increase of work pulse compared to the Vanwonteghem maximum pulse and categorized it into the classification of light or moderate workloads, so this need improvement by taking a short break.